2017
DOI: 10.3390/su10010029
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Farmers’ Pro-Ecological Intentions after Ecological Rehabilitation in a Fragile Environment Area: A Structural Equation Modeling Approach

Abstract: Farmers' pro-ecological intentions (PEI) after ecological rehabilitation are crucial to the sustainability of ecological conservation achievements and attract attention from policy-makers and managers. However, studies regarding multiple factors and their mechanism of influence on farmer's PEI are limited in fragile environmental areas. We conducted a household survey that measures the perceptions and attitudes, and the individual, demographic, and economic properties of 2025 farmers in the Loess Plateau of Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…According to this theory, if farmers experience higher private costs when adopting GPBs in agroforestry, they have a higher probability of adopting them. Additionally, the adoption of GPBs is suggested to be primarily affected by their attitudes, subjective norms, and perceptual behavior control, and studies have shown that these factors are conducive to an individual adopting pro-environmental behaviors [27][28][29]. However, few studies have focused on the agroforestry activities of farmers living in protected areas.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…According to this theory, if farmers experience higher private costs when adopting GPBs in agroforestry, they have a higher probability of adopting them. Additionally, the adoption of GPBs is suggested to be primarily affected by their attitudes, subjective norms, and perceptual behavior control, and studies have shown that these factors are conducive to an individual adopting pro-environmental behaviors [27][28][29]. However, few studies have focused on the agroforestry activities of farmers living in protected areas.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Compared to females, males were more inclined to engage in environmentally friendly behaviours [ 47 ]. Additionally, education level and awareness of environmental improvement affected young male farmers’ participation in the decision-making of rural human settlement environment governance [ 48 ]. TPB theory better explains the relationship between environmental behaviour and willingness of farmers [ 47 ], so it has been widely used in the research of farmers’ environmental behaviour and willingness.…”
Section: Literature Analysismentioning
confidence: 99%
“…From 1958 to 1976 and from 1987 to 2006, the growth rates were 32.65 and 29.71 km/a, respectively. This shortened-or even cut off-the lower reaches of the Manas River, causing the water quality to deteriorate, decreasing biodiversity and limiting the water supply to grasslands, pastures, the oasis margin and the transitional desert zone [31][32][33][34].…”
Section: Changes In the Water System Structurementioning
confidence: 99%